Effects of nanoparticle addition to poly(ε-caprolactone) electrolytes: Crystallinity, conductivity and ambient temperature battery cycling. (20th March 2019) - Eriksson, Therese; Mindemark, Jonas; Yue, Ma; Brandell, Daniel
Abstract: It has previously been shown that nanoparticle additives can, in a simple way, significantly improve the ionic conductivity in solid polymer electrolyte systems with the semi-crystalline poly(ethylene oxide) (PEO) as a host material. It has been suggested that the improved ionic conductivity is a result of reduced degree of crystallinity and additional conductivity mechanisms occurring in the material. In this work, this principle is applied to another semi-crystalline polymer host: poly(ε-caprolactone) (PCL). This is a polymer with comparable properties ( T g, T m, etc. ) as PEO, and constitute a promising material for use in solid polymer electrolytes for lithium ion batteries. 15 wt% of the respective nanoparticles TiO2, Al2 O3 and h-BN have been added to the PCL-LiTFSI solid polymer electrolyte in an attempt to increase the conductivity and achieve stable room temperature cyclability. The crystallinity, ionic conductivity and electrochemical properties were investigated by differential scanning calorimetry, electrochemical impedance spectroscopy and galvanostatic cycling of cells. The results showed that with an addition of 15 wt% Al2 O3, the degree of crystallinity is reduced to 6–7% and the ionic conductivity increased to 6–7 × 10 −6 S cm −1 at room temperature, allowing successful cycling of cells at 30 °C, while h-BN did not contribute to similar improvements. The effect of nanoparticles, however, differ significantly from previous observations in PEO systems, which could be explained by different surface-polymer interactions or the degree of ordering in the amorphous phases of the materials.